Kult cesarski na obszarze prowincji hiszpańskich – rezultat polityki imperialnej Rzymu, czy oddolnej inicjatywy mieszkańców? - Sideł, Damian (Rome and Iberia : Inspirations and Connections throughout History, 2021)
This chapter discusses the issue of the imperial cult on the Iberian Peninsula at the beginnig of the principate. In the first part of the chapter, the stages of development of the imperial cult in the Iberian Peninsula are briefly described. Its main centre was located in Tarraco, the capital city of Hither Spain. Two other provinces – Baetica and Lusitania followed in its footsteps. In the second part, epigraphic and numismatic evidence showing the Iberians’ attitude towards emperor worship are analysed. The author tries to prove that the creation of emperor rituals in the whole Peninsula was dominated by the initiative of the Iberians themsleves.